The status of the in-house marketing research department in large South African companies - L. Pitt; P. Steyn (South African Journal of Business Management, 1986)
Working relations between marketing researchers and managers have merited some attention in marketing literature with particular emphasis on the responsibilities of both parties. In this article the authors report the results of a survey of large South African companies, concerning the level of job satisfaction of marketing research managers; managers' perceptions of in-house marketing research departments; and the perceptions of both parties concerning role expectations of marketing research. Brief attention is also given to the reasons why a majority of companies do not have marketing research departments. Marketing researchers evince a general level of job satisfaction, although there is a measure of dissatisfaction with the procedure for proceeding problems to the research department and also with their role in formulating marketing strategy. Managers mark marketing research departments lower regarding creativity and also on the relevance of marketing research data to decision-making. Significant differences also exist between researchers and managers regarding their role expectations of marketing research. It is evident that these differences in expectations could contribute towards intra-organizational conflict in the marketing department and the recommendation is made that top management give their attention to this matter.
Keywords: 650